Pengaruh Disiplin Kerja, Etos Kerja, Gaya Kepemimpinan, Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Daerah Kota Metro - Maydilla, Putri; Fitriani, Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aims to determine the effect of work discipline, work ethic, leadership style and work environment on employee performance. The type of research used in this research is quantitative research. The object of this research is the Office of the Regional Development Planning Agency of Metro City which is located in Metro City, Metro Pusat. The total population is 61 respondents. Data collection techniques using observation, interviews and questionnaires. Data analysis techniques using SPSS 22 include testing instrument requirements, test requirements analysis, hypothesis testing. Based on the results of the study, it shows that the work discipline variable has an effect and is significant on employee performance, the work ethic variable has an effect and is significant on employee performance, the leadership style variable has an effect and is significant on employee performance, and the work environment variable has no and no significant effect on employee performance. Meanwhile, the simultaneous test of work discipline, work ethic, leadership style and work environment has a significant and significant effect on employee performance.